2012
DOI: 10.1016/j.neuropharm.2012.06.046
|View full text |Cite
|
Sign up to set email alerts
|

AM-251 and rimonabant act as direct antagonists at mu-opioid receptors: Implications for opioid/cannabinoid interaction studies

Abstract: Mu-opioid and CB1-cannabinoid agonists produce analgesia; however, adverse effects limit use of drugs in both classes. Additive or synergistic effects resulting from concurrent administration of low doses of mu- and CB1-agonists may produce analgesia with fewer side effects. Synergism potentially results from interaction between mu-opioid receptors (MORs) and CB1 receptors (CB1Rs). AM-251 and rimonabant are CB1R antagonist/inverse agonists employed to validate opioid-cannabinoid interactions, presumed to act s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 57 publications
5
61
0
Order By: Relevance
“…Many studies have shown this synergistic antinociceptive interaction between cannabinoid and opioid systems (Manzanares et al, 1998(Manzanares et al, , 1999Cichewicz 2004;Cox et al, 2007;Seely et al, 2012). However, the use of cannabis is frequently underreported in our society.…”
Section: Introductionmentioning
confidence: 98%
“…Many studies have shown this synergistic antinociceptive interaction between cannabinoid and opioid systems (Manzanares et al, 1998(Manzanares et al, , 1999Cichewicz 2004;Cox et al, 2007;Seely et al, 2012). However, the use of cannabis is frequently underreported in our society.…”
Section: Introductionmentioning
confidence: 98%
“…The cannabinoid system comprises the two major cannabinoid receptors, CB 1 and CB 2 receptors, their endogenous ligands, anandamide (AEA) and 2-arachidonoylglycerol (2-AG) and enzymes, fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL), which regulate their biosynthesis and degradation (Di Marzo et al, 2004). Simultaneous activation of opioid and cannabinoid receptors can produce synergistic analgesic effects (Smith et al, 1998;Seely et al, 2012). Opioids and cannabinoids produce antinociception through separate (although possibly interrelated) mechanisms (Cichewicz, 2004;Tham et al, 2005;Roberts et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in vitro studies have shown that opioid receptor expression is induced by cannabinoids in Jurkat E6.1 cells via a CB2-dependent mechanism (Borner et al, 2006). Seely et al, (2012) showed that, differently from AM281, a selective CB1 receptor antagonist, AM251 could also acts on µ-opioid receptors. However, the present study clearly showed that AM251 reduces the β-endorphin production induced by AEA and naloxone abolished the fever induced by this cannabinoid suggesting that the anti-opioid effect of AM251 is also related to the endogenous opioids synthesis inhibition.…”
Section: Discussionmentioning
confidence: 99%